Acute management of stroke - I: Ischaemic stroke - Chong, T; Fedi, M (2013)
The adage that 'Time is Brain' remains a cornerstone of acute stroke treatment, and reflects the importance of timely diagnosis and treatment in order to minimise long-term consequences. The greatest advance in the management of ischaemic stroke has come in the form of reperfusion strategies, the success of which relies upon appropriate patient selection and the prompt initiation of therapy. The benefits of intravenous thrombolysis up to 4.5 hours are now firmly established, with trials underway to determine whether certain subgroups may benefit from thrombolysis beyond this timeframe. Intra-arterial thrombolysis has been used for decades but data on its efficacy and safety are limited. Novel methods of reperfusion, such as mechanical clot retrieval and stenting, have high recanalisation rates with acceptable safety and should be considered in patients with mid- to large-sized artery occlusion. Multi-modal reperfusion therapies, which use a combination of pharmacological and endovascular techniques, are showing encouraging results. © 2013 Elsevier Ltd. All rights reserved.